A bimetallic particle modified g-C3N4 photocatalyst and its preparation method, and its application in photocatalytic cellulose-based biomass reforming hydrogen production
By modifying the bimetallic particles of core-shell structure on the g-C3N4 photocatalyst, the dynamic challenges and economic problems in existing photocatalytic technologies are solved, and efficient photocatalytic cellulose-based biomass reforming is achieved.
Patent Information
- Application Number
- CN202410740136.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-07
AI Technical Summary
Existing photocatalytics pose great challenges in the kinetics of decomposing water into hydrogen and oxygen, and the commonly used expensive chemical reagents lead to poor economic performance, and traditional catalysts such as TiO2 and CdS have photocorrosion and toxicity problems.
Bimetallic particles are used to modify graphite carbon nitride (g-C3N4) photocatalysts, and catalytic activity and stability are improved by supporting bimetallic particles with core-shell structures such as Au-Pt, Au-Pd or Ag-Pt on the g-C3N4 support.
The efficiency of photocatalyzed cellulose-based biomass reforming is significantly improved, which is better than the g-C3N4 modified by traditional pure Pt nanoparticles. The process is simple, the preparation time and process are reduced, and the material synthesis yield is improved.
Smart Images

Figure CN118751237B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic hydrogen production, and in particular to a bimetallic particle modified g-C3N4 photocatalyst and a preparation method thereof, and application in photocatalytic cellulose-based biomass reforming hydrogen production. Background Art
[0002] Hydrogen is an ideal substitute for fossil fuels. So far, hydrogen is mainly produced by high-temperature reforming of methane, which has problems such as high energy consumption and high carbon emissions. Photocatalytic water splitting technology can use solar energy to convert water into hydrogen at room temperature and pressure, and is a very promising hydrogen production solution. However, there are huge kinetic challenges in directly decomposing water into hydrogen and oxygen through photocatalysis. At present, chemical reagents such as methanol, triethanolamine, Na2S, lactic acid, and glucose (called sacrificial agents) are usually added to water to eliminate photogenerated holes and improve the efficiency of photogenerated electrons in producing H2. However, these chemical reagents are expensive, and the value of the H2 produced cannot even offset the value of the sacrificial agents consumed, which is not economical. For this reason, using cheap biomass waste to replace these expensive chemical reagents is a current research direction.
[0003] Lignocellulosic biomass is the most abundant and cheapest renewable resource on earth. The world produces up to 100 billion tons of lignocellulosic biomass through photosynthesis every year, but its utilization rate is only about ~10%. Lignocellulosic biomass is mainly composed of cellulose, hemicellulose, and lignin. Compared with conventional small molecule sacrificial agents such as methanol, triethanolamine, Na2S, lactic acid, and glucose, it has a large molecular weight, high degree of polymerization, stable structure, and is more difficult to oxidatively degrade, which places higher requirements on photocatalysts.
[0004] In the past four decades, photocatalytic lignocellulose reforming to produce hydrogen has mainly used TiO2 and CdS as catalysts. However, the former can only absorb ultraviolet light in the wavelength range of less than 400nm, while the latter easily releases CdS during use. 2+ , has high toxicity, photocorrosion problems, and poor stability. Graphitic carbon nitride (g-C3N4) has attracted much attention in the photocatalytic reforming of lignocellulose to produce hydrogen due to its suitable optical band gap (about 2.7eV), excellent chemical stability, and green environmental protection properties. So far, the reported g-C3N4-based photocatalysts mainly use pure Pt nanoparticles as hydrogen production co-catalysts, which have low separation efficiency for photogenerated electrons and low intrinsic catalytic activity for water reduction to produce hydrogen, which greatly limits the efficiency of photocatalytic reforming of lignocellulose to produce hydrogen. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a bimetallic particle modified g-C3N4 photocatalyst and a preparation method thereof, and its application in photocatalytic cellulose-based biomass reforming to produce hydrogen.
[0006] The present invention provides the following technical solutions:
[0007] The present invention provides a bimetallic particle modified g-C3N4 photocatalyst, wherein the catalyst comprises a g-C3N4 carrier and bimetallic particles loaded on the g-C3N4 carrier, wherein the bimetallic particles are one of Au-Pt, Ag-Pt or Au-Pd, and the bimetallic particles are a core-shell structure, with Au or Ag crystals as cores and Pt or Pd atomic clusters as shells.
[0008] The bimetallic core-shell structure of the catalyst can maximize the exposure area of the active metals Pt and Pd, and utilize the synergistic effect between the two metals to greatly improve the capture efficiency of photogenerated electrons and the intrinsic catalytic activity of hydrogen production.
[0009] Furthermore, the loading amount of the bimetallic particles is 4 wt.%, and the mass ratio of different metals in the bimetallic particles is: Au / Pt mass ratio is 3:1-3.9:0.1 or Au / Pd mass ratio is 3:1-3.9:0.1 or Ag / Pt mass ratio is 1:3-3.9:0.1.
[0010] The present invention also provides a method for preparing the above-mentioned bimetallic particle modified g-C3N4 photocatalyst, comprising the following steps:
[0011] (1) Preparation of g-C3N4 nanosheets by thermal polymerization;
[0012] (2) dispersing g-C3N4 nanosheets in an alkaline solution of lignocellulose-based biomass, adding a bimetallic precursor combination, and performing a light deposition treatment under an inert atmosphere to obtain a bimetallic particle-modified g-C3N4 photocatalyst;
[0013] Wherein, the bimetallic precursor combination includes one of an Au, Pt precursor combination, an Au, Pd precursor combination or an Ag, Pt precursor combination.
[0014] The Au-Pt, Au-Pd, and Ag-Pt core-shell bimetallic nanoparticle-modified g-C3N4 nanosheet photocatalyst provided by the present invention is firstly synthesized by a mixed precursor thermal polymerization method, and then Au-Pt, Au-Pd, and Ag-Pt nanoparticles with a core-shell structure are loaded on the nanosheet by a one-step photodeposition method using lignocellulose-based biomass as a sacrificial agent under alkaline conditions.
[0015] In the preparation process of the present invention, lignocellulose-based biomass is used as a sacrificial agent. Compared with sacrificial agents such as glucose, biomass is more difficult to oxidize and consume holes, resulting in a lower concentration of photogenerated electrons on the surface of g-C3N4, which is conducive to the growth of Au into large-sized particles. At the same time, the alkaline environment is not conducive to the formation of metallic Pt nanoparticles. On the contrary, it will promote the hydrolysis of H2PtCl6 into Pt hydroxide, and finally grow on the surface of Au particles in the form of atomic clusters to form a bimetallic core-shell structure. Although the overall size of the bimetallic particles is large, Pt, which is the active center of hydrogen production, is highly dispersed on the surface of Au nanocrystals in the form of atomic clusters, and the exposed active area is larger, the activity is higher, and the bimetallic synergistic effect is more significant.
[0016] Furthermore, the step (1) specifically includes mixing melamine and urea in a mass ratio of 1:10, heating and calcining in a muffle furnace, and grinding the obtained powder to obtain the g-C3N4 nanosheets.
[0017] Furthermore, the heating rate in the muffle furnace was 5°C / min, the calcination temperature was 550°C, and the calcination time was 4h.
[0018] Furthermore, in the step (2), the light deposition treatment further includes centrifugation, washing and drying steps.
[0019] Furthermore, the amount of g-C3N4 is 10-2000 mg, the concentration of g-C3N4 is 0.1-2 mg / mL, the cellulose concentration is 2.5-25 g / L, and the NaOH concentration is 1-5 mol / L; the light source is 395 nm ultraviolet lamp, 365 nm ultraviolet lamp, xenon lamp, sunlight, etc., and the irradiation time is 1-10 h; the drying temperature is 60-80 ° C, and the drying time is 4 h.
[0020] Furthermore, the precursor combination of Au and Pt is HAuCl4 and H2PtCl6, the precursor combination of Au and Pd is HAuCl4 and Na2PdCl4, and the precursor combination of Ag and Pt is AgNO3 and H2PtCl6.
[0021] The present invention also provides the use of a bimetallic particle modified g-C3N4 photocatalyst in photocatalytic cellulose-based biomass reforming hydrogen production.
[0022] When photocatalytic cellulose-based biomass reforming to produce hydrogen is carried out, external mechanical energy and light energy are provided to the reaction system; wherein the external mechanical energy is provided by magnetic stirring, and the light energy is provided by a xenon lamp, an ultraviolet LED lamp or sunlight.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention modifies the surface of g-C3N4 photocatalyst with a core-shell bimetallic co-catalyst, using active metals such as Pt and Pd as the shell layer to fully expose the reaction active sites. Secondly, the synergistic effect between the bimetallics is utilized to greatly improve the capture efficiency of photogenerated electrons and the intrinsic catalytic activity of hydrogen production. Compared with the traditional g-C3N4 modified with pure Pt nanoparticles, the efficiency of hydrogen production from photocatalytic cellulose-based biomass reforming can be greatly improved.
[0025] 2. The present invention improves the preparation of g-C3N4 nanosheet photocatalysts. Using a mixture of urea and melamine as a precursor, g-C3N4 nanosheets are obtained by calcination through thermal polymerization. Compared with the use of pure urea precursor, the product has similar morphology and activity, but the material synthesis yield is increased several times.
[0026] 3. The bimetallic loading method adopted in the present invention is a one-step photodeposition method using cellulose or lignocellulose as a sacrificial agent under alkaline conditions. The preparation process is simple, and compared with the step-by-step photodeposition method, the preparation time and process are reduced by half, greatly improving the preparation efficiency. At the same time, within a certain metal ratio range, Au-Pt, Au-Pd, and Ag-Pt bimetallic nanoparticles with core-shell structures can be obtained, with a larger active metal exposure area, higher activity, and more significant synergistic effect.
[0027] 4. The g-C3N4 modified with bimetallic nanoparticles obtained in the present invention can be widely used in the reforming and hydrogen production of various lignocellulose-based biomass, including branches, leaves, straw, waste paper, cotton cloth, etc.
[0028] 5. Under the irradiation of a 300W xenon lamp, the photocatalyst prepared by the present invention has a maximum hydrogen production rate of 1061.8 μmol / g / h for Au-Pt / g-C3N4, a maximum hydrogen production rate of 620.4 μmol / g / h for Au-Pd / g-C3N4, and a maximum hydrogen production rate of 652.7 μmol / g / h for Ag-Pt / g-C3N4, all of which are superior to the performance of pure metal catalysts with corresponding mass. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A flow chart of a preparation method provided by an embodiment of the present invention;
[0031] Figure 2is an XRD pattern of Au-Pt / g-C3N4 materials with different Au / Pt ratios provided in the first embodiment of the present invention;
[0032] Figure 3A to Figure 3C TEM images of Pt1Au3 / g-C3N4 material, Au4 / g-C3N4, and Pt4 / g-C3N4 material and the corresponding metal particle size distribution ( Figure 3A For Pt1Au3 / g-C3N4 material, Figure 3B For Au4 / g-C3N4 material, Figure 3C is Pt4 / g-C3N4 material);
[0033] Figure 4A to Figure 4E The structural characterization data of the core-shell bimetallic nanoparticles in the Pt1Au3 / g-C3N4 photocatalyst and the schematic diagram of the structure of the Au-Pt core-shell bimetallic nanoparticles provided in the first embodiment of the present invention;
[0034] Figure 5 It is a UV-visible diffuse reflectance spectrum (DRS) diagram of Pt4 / g-C3N4, Pt3Au1 / g-C3N4, Pt1Au3 / g-C3N4, Au4 / g-C3N4 materials and g-C3N4 provided in the first embodiment of the present invention;
[0035] Figure 6 A HAADF-EDS Mapping diagram of the Pd1Au3 / g-C3N4 material provided in the second embodiment of the present invention;
[0036] Figure 7 A HAADF-EDS Mapping diagram of the Ag1Pt3 / g-C3N4 material provided in the third embodiment of the present invention;
[0037] Figure 8A to Figure 8B It is a photocatalytic cellulose reforming activity diagram of Pt4 / g-C3N4, Pt3Au1 / g-C3N4, Pt2Au2 / g-C3N4, Pt1Au3 / g-C3N4, and Au4 / g-C3N4 provided in the first embodiment of the present invention;
[0038] Figure 9A to Figure 9B is a graph showing the variation of the photocatalytic activity of the Pt1Au3 / g-C3N4 material with the cellulose concentration and the NaOH concentration provided in the first embodiment of the present invention;
[0039] Fig.10 is a photocatalytic cellulose reforming stability performance diagram of the Pt1Au3 / g-C3N4 material provided in the first embodiment of the present invention;
[0040] Fig.11This is a diagram of hydrogen production from the photocatalytic reforming of different biomasses by Pt1Au3 / g-C3N4 material provided in the first embodiment of the present invention;
[0041] Fig.12 It is a photocatalytic cellulose reforming activity diagram of Au-Pd / g-C3N4 materials modified with metal nanoparticles of different components provided in the second embodiment of the present invention;
[0042] Fig.13 This is a photocatalytic cellulose reforming activity diagram of Ag-Pt / g-C3N4 materials modified with metal nanoparticles of different components provided in the third embodiment of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] An embodiment of the present invention provides a bimetallic particle modified g-C3N4 photocatalyst, wherein the catalyst includes a g-C3N4 carrier and bimetallic particles loaded on the g-C3N4 carrier, wherein the bimetallic particles are one of Au-Pt, Ag-Pt or Au-Pd, and the bimetallic particles are a core-shell structure with Au or Ag crystals as the core and Pt or Pd atomic clusters as the shell.
[0045] Among them, the size of Au-Pt bimetallic particles is 6 to 13 nm, the size of Au-Pd bimetallic particles is 3 to 12 nm, and the size of Ag-Pt bimetallic particles is 4 to 12 nm.
[0046] The loading amount of the bimetallic particles is 4 wt.%, and the mass ratio of different metals in the bimetallic particles is: Au / Pt mass ratio is 3:1-3.9:0.1 or Au / Pd mass ratio is 3:1-3.9:0.1 or Ag / Pt mass ratio is 1:3-3.9:0.1.
[0047] The present invention also provides a method for preparing a bimetallic particle modified g-C3N4 photocatalyst, comprising the following steps:
[0048] Preparation of g-C3N4 nanosheets by thermal polymerization;
[0049] The g-C3N4 nanosheets are dispersed in an alkaline solution of lignocellulose-based biomass, a bimetallic precursor combination is added, and a light deposition treatment is performed under an inert atmosphere to obtain a bimetallic particle-modified g-C3N4 photocatalyst; wherein the bimetallic precursor combination includes one of an Au, Pt precursor combination, an Au, Pd precursor combination or an Ag, Pt precursor combination.
[0050] like Figure 1 As shown, the steps are specifically as follows:
[0051] S101, preparing g-C3N4 material by thermal polymerization method;
[0052] S102, dispersing the g-C3N4 material in a cellulose aqueous solution containing NaOH, adding a precursor mixture of Au and Pt, Au and Pd, Ag and Pt to perform a photodeposition treatment;
[0053] S103. Centrifuge the photodeposition product, wash it to neutrality and then dry it to obtain Au-Pt / g-C3N4, Au-Pd / g-C3N4 and Ag-Pt / g-C3N4 photocatalysts.
[0054] The present invention will be further described below by means of specific examples.
[0055] In the first embodiment, the preparation process of Au-Pt bimetallic nanoparticles modified g-C3N4 photocatalyst is as follows:
[0056] (1) Preparation of g-C3N4 nanosheets
[0057] 1 g of melamine and 10 g of urea were placed in a covered crucible, mixed well and then heated to 550 °C in a muffle furnace at a rate of 5 °C / min and maintained for 4 h. The obtained powder was ground into powder for further use.
[0058] (2) Preparation of Au-Pt bimetallic nanoparticles modified g-C3N4 photocatalyst
[0059] 10 mg g-C3N4, 0.2 g cellulose, and 2.4 g NaOH were ultrasonically dispersed in 20 mL deionized water, and a certain amount of HAuCl4 and H2PtCl6 were added to the mixture to achieve a total metal loading of 4 wt.% (sample named Pt 4-x Au x / g-C3N4, where x=0-4). After purging with argon for 10 min, the reactor was sealed and irradiated with a 300W xenon lamp for 2 h. Centrifugation was performed, and the sample was washed with deionized water and anhydrous ethanol until neutral. After drying in a forced air drying oven at 60°C for 4 h, the Au-Pt bimetallic nanoparticle-modified g-C3N4 photocatalyst was obtained.
[0060] For example:
[0061] When x = 0 or 4, single metal modified Pt4 / g-C3N4 or Au4 / g-C3N4 is obtained;
[0062] When x = 1, the obtained material is Pt3Au1 / g-C3N4 modified with bimetallic nanoparticles;
[0063] When x = 2, the obtained material is Pt2Au2 / g-C3N4 modified with bimetallic nanoparticles;
[0064] When x=3, what is obtained is Pt1Au3 / g-C3N4 modified with bimetallic nanoparticles.
[0065] x is not limited to the above values, and x can be 0.1, 0.5, 1.1, 1.5, 2.1, 2.5, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, etc., and any value within the range of 0 to 4 is acceptable.
[0066] The above-prepared materials were tested and analyzed: Figure 2 The XRD patterns of g-C3N4 materials modified with different Au-Pt core-shell bimetallic nanoparticles and g-C3N4 materials modified with Au and Pt single metal nanoparticles provided in the first embodiment of the present invention show that the bimetallic particles on the g-C3N4 nanosheets only show the diffraction peaks of metallic Au, and do not show the peaks of Pt or PtO, indicating that Au exists in the form of metal nanoparticles, while Pt exists in the form of atomic clusters.
[0067] Figure 3A to Figure 3C The TEM images and corresponding metal particle size distributions of the g-C3N4 material modified with Pt1Au3 bimetallic nanoparticles and the g-C3N4 material modified with Au and Pt single metal nanoparticles provided in the first embodiment of the present invention are shown. It can be seen that the metal nanoparticles are uniformly modified on the surface of the g-C3N4 nanosheets, wherein the size of the Au-Pt bimetallic nanoparticles is 6.4 to 12.8 nm.
[0068] Figure 4A to Figure 4E The structural characterization data of the core-shell bimetallic nanoparticles in the Pt1Au3 / g-C3N4 photocatalyst provided in the first embodiment of the present invention and the schematic diagram of the structure of the Au-Pt core-shell bimetallic nanoparticles. Figure 4AThe results show that Au-Pt metal particles have a core-shell structure. The highly crystalline nanoparticles constitute the core, which is surrounded by a loose atomic layer with a thickness of 1-2nm. The metal core shows a polycrystalline structure with a lattice spacing of 0.24nm, which is consistent with the (111) crystal plane of metal Au. The EDS energy spectrum distribution diagram shows that the Au and Pt signals on the nanoparticles are basically evenly distributed. However, a closer look reveals that Pt shows a slightly wider distribution than Au, indicating that the metal particles may form a structure with Au particles as the core and Pt atoms or clusters as the shell. Figure 4B The EXAFS results show that the Au in the Au-Pt bimetallic exists mainly in the form of Au-Au coordination, and is mainly composed of metallic Au particles. Figure 4C The EXAFS results show that Pt in the Au-Pt bimetallic exists mainly in the form of Pt-O coordination, mainly in the form of Pt atoms or atomic clusters. Figure 4D This is the in situ diffuse reflectance infrared spectrum of CO absorption, proving that the surface of Au-Pt bimetallic is coated by Pt atoms or atomic clusters. Figure 4E Schematic diagram of the structure of Au-Pt core-shell bimetallic nanoparticles inferred based on the above characterization results.
[0069] In this embodiment, when the mass ratio of Pt is small and the size of the Au core is large, it is easy to form a core-shell structure in which Pt is dispersed around the core. A core-shell bimetallic structure can be formed when the Au / Pt mass ratio is 3:1 to 3.9:0.1.
[0070] Figure 5 The UV-visible diffuse reflectance spectra (DRS) of the g-C3N4 material modified with Au-Pt bimetallic nanoparticles and the g-C3N4 material modified with Au and Pt single metal nanoparticles provided in the first embodiment of the present invention show that the loaded metal co-catalyst improves the absorption in the entire visible light range.
[0071] In the second embodiment, the preparation process of Au-Pd bimetallic nanoparticles modified g-C3N4 photocatalyst is as follows:
[0072] (1) Preparation of g-C3N4 nanosheets
[0073] 1 g of melamine and 10 g of urea were placed in a covered crucible, mixed well, and then heated to 550 °C in a muffle furnace at a rate of 5 °C / min and maintained for 4 h. The obtained powder was ground into powder for further use.
[0074] (2) Preparation of Au-Pd bimetallic nanoparticles modified g-C3N4 photocatalyst
[0075] 10 mg g-C3N4, 0.2 g cellulose, and 2.4 g NaOH were ultrasonically dispersed in 20 mL deionized water, and a certain amount of HAuCl4 and Na2PdCl4 were added to the mixture to achieve a total metal loading of 4 wt.% (sample named Pd 4-x Au x / g-C3N4, where x=0-4). After purging with argon for 10 min, the reactor was sealed and irradiated with a 300W xenon lamp for 2 h. Centrifugation was performed, and the sample was washed with deionized water and anhydrous ethanol until neutral. After drying in a forced air drying oven at 60°C for 4 h, the Au-Pd bimetallic nanoparticle-modified g-C3N4 photocatalyst was obtained.
[0076] For example:
[0077] When x = 0 or 4, single metal modified Pd4 / g-C3N4 or Au4 / g-C3N4 is obtained;
[0078] When x = 1, the obtained material is Pd3Au1 / g-C3N4 modified with bimetallic nanoparticles;
[0079] When x = 2, the obtained material is Pd2Au2 / g-C3N4 modified with bimetallic nanoparticles;
[0080] When x=3, what is obtained is Pd1Au3 / g-C3N4 modified with bimetallic nanoparticles.
[0081] x is not limited to the above values, and x can be 0.1, 0.5, 1.1, 1.5, 2.1, 2.5, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, etc., and any value within the range of 0 to 4 is acceptable.
[0082] See also Figure 6 , is the HAADF-EDS Mapping diagram of Pd1Au3 / g-C3N4, indicating that Pd1Au3 forms a core-shell structure with Au as the core and Pd as the shell.
[0083] In this embodiment, when the Pd mass ratio is small and the Au core size is large, it is easy to form a core-shell structure in which Pd is highly dispersed around the core. A core-shell bimetallic structure can be formed when the Au / Pd mass ratio is 3:1 to 3.9:0.1.
[0084] In the third embodiment, the preparation process of Ag-Pt bimetallic nanoparticles modified g-C3N4 photocatalyst is as follows:
[0085] (1) Preparation of g-C3N4 nanosheets
[0086] 1 g of melamine and 10 g of urea were placed in a covered crucible, mixed well, and then heated to 550 °C in a muffle furnace at a rate of 5 °C / min and maintained for 4 h. The obtained powder was ground into powder for further use.
[0087] (2) Preparation of Ag-Pt bimetallic nanoparticles modified g-C3N4 photocatalyst
[0088] 10 mg g-C3N4, 0.2 g cellulose, and 2.4 g NaOH were ultrasonically dispersed in 20 mL deionized water, and a certain amount of AgNO3 and H2PtCl6 were added to the mixture to achieve a total metal loading of 4 wt.% (sample named Pt 4-x Ag x / g-C3N4, where x=0-4). After purging with argon for 10 min, the reactor was sealed and irradiated with a 300W xenon lamp for 2 h. Centrifugation was performed, and the sample was washed with deionized water and anhydrous ethanol until neutral. After drying in a forced air drying oven at 60°C for 4 h, the Ag-Pt bimetallic nanoparticle-modified g-C3N4 photocatalyst was obtained.
[0089] For example:
[0090] When x = 0 or 4, single metal modified Pt4 / g-C3N4 or Ag4 / g-C3N4 is obtained;
[0091] When x = 1, the obtained material is Pt3Ag1 / g-C3N4 modified with bimetallic nanoparticles;
[0092] When x = 2, the obtained material is Pt2Ag2 / g-C3N4 modified with bimetallic nanoparticles;
[0093] When x=3, what is obtained is Pt1Ag3 / g-C3N4 modified with bimetallic nanoparticles.
[0094] x is not limited to the above values, and x can be 0.1, 0.5, 1.1, 1.2, 1.3, 1.5, 1.9, 2.1, 2.5, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, etc., and any value within the range of 0 to 4 is acceptable.
[0095] See also Figure 7 , is the HAADF-EDS Mapping diagram of Ag1Pt3 / g-C3N4, indicating that Ag1Pt3 generates a core-shell structure with Ag as the core and Pt as the shell.
[0096] In this embodiment, when the mass ratio of Pt is small and the size of the Ag core is large, it is easy to form a core-shell structure in which Pt is highly dispersed around the core. A core-shell bimetallic structure can be formed when the Ag / Pt mass ratio is 1:3 to 3.9:0.1.
[0097] Application Example 1
[0098] (1) Au-Pt / g-C3N4 photocatalytic cellulose reforming hydrogen production effect:
[0099] 10 mg of each sample prepared in the first embodiment was placed in a sample bottle, and 20 mL of NaOH alkaline solution (3 mol / L) containing 10 g / L cellulose was added to each sample bottle. Before the experiment, a low flow of high-purity argon gas was continuously passed through each sample bottle for 10 min, and the air in the bottle was exhausted. After being sealed, it was placed in a magnetic stirrer and heated by a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, catalytic reaction time 1 ~ 4h, the use of syringe to collect 100μL gaseous products, and injected into the gas chromatograph (s■sun GC-9860) to detect the H2 production, calculate the hydrogen production rate. The results of hydrogen production rate of different samples are shown in Table 1 and Figure 8A to Figure 8B shown.
[0100] Table 1 Test results
[0101]
[0102] From Table 1 and Figure 8A to Figure 8B It can be seen that the Au-Pt bimetallic nanoparticle-modified g-C3N4 nanosheets prepared in the present invention have good photocatalytic cellulose reforming hydrogen production effect, among which the activity of the sample Pt1Au3 / g-C3N4 (loaded with 3wt.% Au and 1wt.% Pt) is increased by 6.8 times and 14 times compared with Pt4 / g-C3N4 and Au4 / g-C3N4, respectively.
[0103] (2) Effect of different cellulose dosage on Au-Pt / g-C3N4 photocatalytic cellulose reforming to produce hydrogen:
[0104] 10 mg of the prepared Pt1Au3 / g-C3N4 sample was placed in a sample bottle, and 20 mL of NaOH alkaline solution (3 mol / L) containing different concentrations of cellulose (i.e., 0, 0.5, 2.5, 5, 10, 15, 25, 50, 100 g / L) was added. A low flow of high-purity argon gas was continuously introduced into the sample bottle for 10 min, and the air in the bottle was exhausted. After sealing, the bottle was placed on a magnetic stirrer and illuminated with a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, photocatalytic reaction for 1 to 4 h, every 1 h with a syringe to collect 100 μL of gaseous products, and injected into the gas chromatograph (s·sun GC-9860) to detect the H2 production, hydrogen production rate as Fig. 9A shown.
[0105] (3) Effect of different NaOH concentrations on Au-Pt / g-C3N4 photocatalytic cellulose reforming to produce hydrogen:
[0106] 10 mg of the prepared Pt1Au3 / g-C3N4 sample was placed in a sample bottle, and 20 mL of NaOH alkaline solution containing 10 g / L cellulose of different concentrations (i.e., 0, 0.125, 1, 3, 5, 10 mol / L) was added. A low flow of high-purity argon gas was continuously introduced into the sample bottle for 10 min, and the air in the bottle was exhausted. After sealing, the bottle was placed on a magnetic stirrer and heated with a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, photocatalytic reaction for 1 to 4 hours, every 1 hour with a syringe to collect 100 μL of gaseous products, and injected into the gas chromatograph (s■sun GC-9860) to detect the H2 production, hydrogen production rate as shown in Fig. 9B shown.
[0107] Figure 9A to Figure 9B The photocatalytic activity of Pt1Au3 / g-C3N4 provided in Example 2 of the present invention shows that the H2 generation rate is highly correlated with the concentrations of NaOH and cellulose, and the absence of either one can completely inhibit the generation of H2 ( Figure 9A to Figure 9B ). The optimal concentration range of cellulose is 2.5-15g / L, which can ensure the H2 production rate is above 1000μmol / g / h. Excessive cellulose may hinder the propagation of light in the solution, thereby inhibiting the photocatalytic reaction. The optimal concentration of NaOH is 3mol / L. Excessive NaOH will lead to a higher solution viscosity, reducing the rate of hydrogen production by photocatalytic cellulose reforming.
[0108] (4) Stability test of Au-Pt / g-C3N4 photocatalytic cellulose reforming to produce hydrogen:
[0109] 10 mg of the prepared Pt1Au3 / g-C3N4 sample was placed in a sample bottle, and 20 mL of a 3 mol / L NaOH alkaline solution containing 10 g / L cellulose was added. A low flow of high-purity argon gas was continuously introduced into the sample bottle for 10 min, and the air in the bottle was exhausted. The bottle was sealed and placed on a magnetic stirrer, and a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, the catalytic reaction continued for 13 hours, and 100 μL of gaseous products were collected by syringe every 1 hour and injected into a gas chromatograph (s■sun GC-9860) to detect H2 production. The test results are shown in Fig.10 As shown, it indicates that the catalytic activity is basically maintained after 13 hours of testing.
[0110] (5) Photocatalytic hydrogen production effect of different lignocellulose and other biomasses:
[0111] 10 mg of the prepared Pt1Au3 / g-C3N4 sample was placed in a sample bottle, and 20 mL of NaOH alkaline solution (3 mol / L) and 10 mg of different lignocellulose and other biomass (starch, hemicellulose, lignin, paper, cotton, wood, grass, leaves, branches, etc.) were added. A low flow of high-purity argon gas was continuously introduced into the sample bottle for 10 minutes, and the air in the bottle was exhausted. After sealing, it was placed on a magnetic stirrer and heated with a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, photocatalytic reaction for 1 to 4 hours, every 1 hour, 100 μL of gaseous products were collected with a syringe and injected into a gas chromatograph (s■sun GC-9860) to detect H2 production.
[0112] The hydrogen production rate is Fig.11 As shown, Fig.11 The hydrogen production efficiency diagram of the photocatalytic reforming of different biomasses such as lignocellulose by Pt1Au3 / g-C3N4 provided by the present invention. The results show that the hydrogen production efficiency of different biomasses varies greatly. The hydrogen production efficiency of discarded napkins can reach 780μmol / g / h. Among natural biomasses, the hydrogen production efficiency of biomass such as soapberry branches and sedge grass can reach about 400μmol / g / h.
[0113] Application Example 2
[0114] Au-Pd / g-C3N4 Photocatalytic Reforming of Cellulose to Produce Hydrogen
[0115] 10 mg of each sample prepared in the second embodiment was placed in a sample bottle, and 20 mL of a 3 mol / L NaOH alkaline solution containing 10 g / L cellulose was added to each sample bottle. Before the experiment, a low flow of high-purity argon gas was continuously introduced into each sample bottle for 10 min, and the air in the bottle was exhausted. After being sealed, the bottle was placed in a magnetic stirrer and heated with a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, catalytic reaction time 1 ~ 4h, the use of syringe to collect 100μL gaseous products, and injected into the gas chromatograph (s■sun GC-9860) to detect the H2 production, calculate the hydrogen production rate. The results of hydrogen production rate of different samples are shown in Table 2 and Fig.12 shown.
[0116] Table 2 Test results
[0117]
[0118] From Table 2 and Fig.12It can be seen that the Au-Pd bimetallic nanoparticle-modified g-C3N4 nanosheets prepared in the present invention have good photocatalytic cellulose reforming hydrogen production effect, among which the activity of the sample Pd1Au3 / g-C3N4 (loaded with 3wt.% Au and 1wt.% Pd) is increased by 5.1 times and 7.7 times compared with Pd4 / g-C3N4 and Au4 / g-C3N4, respectively.
[0119] Application Example 3
[0120] Photocatalytic reforming of cellulose to produce hydrogen over Ag-Pt / g-C3N4
[0121] 10 mg of each sample prepared in the third embodiment was placed in a sample bottle, and 20 mL of NaOH alkaline solution (3 mol / L) containing 10 g / L cellulose was added to each sample bottle. Before the experiment, a low flow of high-purity argon gas was continuously introduced into each sample bottle for 10 min, and the air in the bottle was exhausted. After being sealed, it was placed in a magnetic stirrer and heated by a 300 W xenon lamp (with an optical power density of 150 mW / cm 2 ) irradiation, catalytic reaction time 1 ~ 4h, the use of syringe to collect 100μL gaseous products, and injected into the gas chromatograph (s■sun GC-9860) to detect the H2 production, calculate the hydrogen production rate. The results of hydrogen production rate of different samples are shown in Table 3 and Fig.13 shown.
[0122] Table 3 Test results
[0123]
[0124] From Table 3 and Fig.13 It can be seen that the g-C3N4 nanosheets modified with Ag-Pt bimetallic nanoparticles prepared in the present invention have good photocatalytic cellulose reforming hydrogen production effect, among which the activity of the sample Pt3Ag1 / g-C3N4 (loaded with 3wt.% Pt and 1wt.% Ag) is increased by 4.7 times and 186.6 times compared with Pt4 / g-C3N4 and Ag4 / g-C3N4, respectively.
[0125] Lignocellulose-based biomass exists in large quantities in nature, and social life also produces a large amount of cellulose-rich waste items such as waste paper and old clothes. At present, how to make high-value use of these lignocellulose-rich wastes is a major problem. Studies have shown that photocatalytic lignocellulose reforming to produce hydrogen is a potential technology for treating such biomass wastes. It replaces expensive sacrificial agents such as methanol and triethanolamine with lignocellulose, eliminates holes generated by light excitation of semiconductors, and thus improves hydrogen production efficiency. This reaction can produce clean fuel H2 while decomposing biomass, killing two birds with one stone. At present, the reaction is mainly based on TiO2 and CdS photocatalysts. The former can only work under ultraviolet light, and the latter easily releases highly toxic Cd 2+ , and the stability is poor. Pt / g-C3N4 is a type of clean, safe and visible light responsive lignocellulose reforming hydrogen production photocatalyst, but its hydrogen production performance is limited to a large extent by pure Pt co-catalyst. The present invention is the first to modify the surface of g-C3N4 with Au-Pt, Au-Pd, Ag-Pt and other core-shell bimetallic co-catalysts by a one-step photodeposition method in a lignocellulose-based biomass environment under alkaline conditions. The bimetallic particles are core-shell structures, and their Au or Ag metal nanoparticle cores are more conducive to capturing photoelectrons, and are also conducive to the dispersion of Pt or Pd clusters on their surfaces. The special structure and synergistic effect of the bimetallic are used to increase the exposed surface of the active metal, adjust the capture efficiency of photogenerated electrons and the intrinsic catalytic activity, and improve the efficiency of photocatalytic hydrogen production. The experimentally obtained Au-Pt / g-C3N4, Au-Pd / g-C3N4, and Ag-Pt / g-C3N4 photocatalytic cellulose reforming hydrogen production performance is significantly better than that of single metal modified photocatalysts such as Pt / g-C3N4, Au / g-C3N4, Pd / g-C3N4, and Ag / g-C3N4.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. Application of a bimetallic particle modified g-C3N4 photocatalyst in photocatalytic cellulose-based biomass reforming hydrogen production, characterized in that: The preparation method of the bimetallic particle modified g-C3N4 photocatalyst comprises the following steps: (1) Preparation of g-C3N4 nanosheets by thermal polymerization; (2) dispersing g-C3N4 nanosheets in an alkaline solution of lignocellulose-based biomass, adding a bimetallic precursor combination, and performing a light deposition treatment under an inert atmosphere to obtain a bimetallic particle-modified g-C3N4 photocatalyst; Wherein, the bimetallic precursor combination includes one of an Au and Pt precursor combination, an Au and Pd precursor combination or an Ag and Pt precursor combination; the Au and Pt precursor combination is HAuCl4 and H2PtCl6, the Au and Pd precursor combination is HAuCl4 and Na2PdCl4, and the Ag and Pt precursor combination is AgNO3 and H2PtCl6; The bimetallic particle modified g-C3N4 photocatalyst includes a g-C3N4 carrier and bimetallic particles loaded on the g-C3N4 carrier, the bimetallic particles are one of Au-Pt, Ag-Pt or Au-Pd, the bimetallic particles are a core-shell structure, with Au or Ag crystals as the core and Pt or Pd atomic clusters as the shell; the loading amount of the bimetallic particles is 4wt.%, and the mass ratio of different metals in the bimetallic particles is: Au / Pt mass ratio is 3:1~3.9:0.1 or Au / Pd mass ratio is 3:1~3.9:0.1 or Ag / Pt mass ratio is 1:3~3.9:0.
1.
2. The use of the bimetallic particle modified g-C3N4 photocatalyst as claimed in claim 1 in photocatalytic reforming of cellulose-based biomass to produce hydrogen, characterized in that: The step (1) specifically comprises mixing melamine and urea in a mass ratio of 1:10, heating and calcining in a muffle furnace, and grinding the obtained powder to obtain the g-C3N4 nanosheets.
3. The use of the bimetallic particle modified g-C3N4 photocatalyst as claimed in claim 2 in photocatalytic reforming of cellulose-based biomass to produce hydrogen, characterized in that: The heating rate in the muffle furnace was 5°C / min, the calcination temperature was 550°C, and the calcination time was 4h.
4. The use of the bimetallic particle modified g-C3N4 photocatalyst as claimed in claim 1 in photocatalytic reforming of cellulose-based biomass to produce hydrogen, characterized in that: In the step (2), the light deposition treatment further includes centrifugation, washing and drying steps.
5. The use of the bimetallic particle modified g-C3N4 photocatalyst as claimed in claim 1 in photocatalytic cellulose-based biomass reforming hydrogen production, characterized in that: The dosage of g-C3N4 is 10~2000mg, the concentration of g-C3N4 is 0.1~2 mg / mL, the cellulose concentration is 2.5~25g / L, and the NaOH concentration is 1~5 mol / L; the light source is 395 nm ultraviolet lamp, 365nm ultraviolet lamp, xenon lamp or sunlight, and the irradiation time is 1~10h; the drying temperature is 60~80℃, and the drying time is 4h.
Citation Information
Patent Citations
Preparation method and application of g-C3N4 nanosheet photocatalyst
CN116550357A
Bimetal core-shell structure nanocrystalline composite catalyst, preparation method and application
CN116695144A